A Japanese Patient with Genitopatellar Syndrome Transiently Presenting with Cardiac Intramural Cavity during the Neonatal Period. (29th August 2020) - Takahashi, Kiichi; Adachi, Hiroyuki; Toyono, Manatomo; Ito, Masato; Kato, Akie; Noguchi, Atsuko; Takahashi, Tsutomu
Abstract : Genitopatellar syndrome (GPS) is a rare autosomal dominant disorder caused by de novo pathogenic variants in the KAT6B gene. It is characterized by genital abnormalities, patellar hypoplasia/agenesis, flexion contractures of the hips and knees, corpus callosum agenesis with microcephaly, and hydronephrosis and/or multiple renal cysts. More than half of patients with GPS have congenital heart defects, mostly atrial and/or ventricular septal defects, patent foramen ovale, and patent ductus arteriosus. We report a case of a Japanese neonate with a de novo heterozygous c.3769_3772delTCTA pathogenic variant in the KAT6B gene who presented with a cardiac intramural cavity of the ventricular septum at birth. The cavity unexpectedly disappeared at 1 month of age, but trabecular septal thinning and flash remained. The features of the cavity were not consistent with those of congenital ventricular diverticulum or aneurysm, and its identity and prognosis are still unclear. Because patients with GPS may exhibit various forms of cardiac malformation, careful cardiac examination and follow-up are required from birth in cases of suspected GPS.